2019
DOI: 10.1177/1053825919869367
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Fatigue Within Summer Camp: Perspectives From Camp Health Care Providers and Directors

Abstract: Background: Summer camps engage millions of youth in enrichment opportunities during the summertime while employing a substantial young adult workforce to provide high-quality programs and services to camp participants. Workplace fatigue has been implicated in camp-related injury and illness events, yet few studies have targeted fatigue among camp employees. Purpose: This study aimed to better understand how fatigue impacted employee performance as well as strategies for reducing the negative impacts of fatigu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…These authors also observed that the investment in training could increase staff retention. Similarly, Dubin et al (2020) concluded it was essential to identity fatigue causes, and that improving privacy and personal space at camp and access to technology could help alleviate staff fatigue. It was also proposed to incentivise staff to use their time-off for sleeping, reduce the program of activities, and allow staff to have more time in passive supervision and relaxation activities.…”
Section: Human Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors also observed that the investment in training could increase staff retention. Similarly, Dubin et al (2020) concluded it was essential to identity fatigue causes, and that improving privacy and personal space at camp and access to technology could help alleviate staff fatigue. It was also proposed to incentivise staff to use their time-off for sleeping, reduce the program of activities, and allow staff to have more time in passive supervision and relaxation activities.…”
Section: Human Resourcesmentioning
confidence: 99%
“…This is evidsent by growing numbers of publications in the sport and physical education literature, including opinion articles (e.g., HENDERSON, 2018), special issues (e.g., BIALESCHKI; BROWNE, 2018), or specific sources for industry trends (e.g., Camping Magazine), which has led to two main areas of camp study: outcomes and operations (HENDERSON et al, 2007). A large part of recent publications covers participation outcomes (e.g., WEAVER et al, 2014), while some focus on operational (HENDERSON et al, 2007) or managerial aspects as camp safety (e.g., CHANG et al, 2017), consumer behaviour (e.g., OMELAN et al, 2018), or staff (e.g., DUBIN et al, 2020). This dispersion of information has limited critical discussion on how child camp management processes can be improved.…”
Section: Introductionmentioning
confidence: 99%
“…What is more, while caring for campers who are living at camp, counselors themselves are also living away from their own homes and support systems. This necessitates the completion of a number of tasks related to their own well-being such as laundry, attending events, and enrolling in university courses (Baker, 2020;Dubin et al, 2020;Rubin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, research on camp staff experiences suggests staff must juggle multiple demands, both invigorating and draining. In addition to creating a caring and supportive context in which camp and personal values can be transmitted (Rubin et al, 2018; Sorenson, 2018) and camper development can be promoted (Henderson et al, 2007; Wallace, 2008; Wilson et al, 2019), camp staff are also responsible for handling demanding camp schedules, managing camper behavioral issues, completing paperwork, and participating in fundraising, all with a relative lack of privacy or time off during the summer months (Dubin et al, 2020; Hall et al, 2020). What is more, while caring for campers who are living at camp, counselors themselves are also living away from their own homes and support systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation